2020
DOI: 10.3390/ijms21186717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KLF4 on Cell Proliferation and Epithelial Differentiation in the Context of Cystic Fibrosis

Abstract: Cystic fibrosis (CF) cells display a more cancer-like phenotype vs. non-CF cells. KLF4 overexpression has been described in CF and this transcriptional factor acts as a negative regulator of wt-CFTR. KLF4 is described as exerting its effects in a cell-context-dependent fashion, but it is generally considered a major regulator of proliferation, differentiation, and wound healing, all the processes that are also altered in CF. Therefore, it is relevant to characterize the differential role of KLF4 in these proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Crespin et al, 2014 [198] Primary cell lines: non-CF and CF nasal and bronchial epithelial cells. Sousa et al, 2020 [200] α1AT: alpha-1 antitrypsin; HDMF: 4-hydroxy-2,5-dimethyl-3(2H)-Furanone; NE: neutrohil elastase.…”
Section: Submerged On Plasticmentioning
confidence: 99%
See 3 more Smart Citations
“…Crespin et al, 2014 [198] Primary cell lines: non-CF and CF nasal and bronchial epithelial cells. Sousa et al, 2020 [200] α1AT: alpha-1 antitrypsin; HDMF: 4-hydroxy-2,5-dimethyl-3(2H)-Furanone; NE: neutrohil elastase.…”
Section: Submerged On Plasticmentioning
confidence: 99%
“…Further work was done to assess the impact of KLF4 in TEER acquisition and wound repair, using the isogenic pair wt-CFTR and F508del-CFTR-CFBE cells and their respective KLF4 knockout (KO) counterparts (via CRISPR-Cas9) [ 200 ] in polarized conditions. CF cells showed a higher proliferation rate than non-CF cells (as evaluated by Ki-67 staining and growth curve), which, however, was not influenced by KLF4 KO.…”
Section: Airway Epithelial Regeneration Wound Repair and Cfmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we recently found that knocking-out (KO) KLF4, a transcription factor known to regulate epithelial differentiation among other processes [ 41 , 42 ], in polarized wt-CFTR-expressing bronchial epithelial (CFBE) cells leads to a significant decrease in TEER. The opposite was seen in F508del-CFTR-expressing cells upon KLF4-KO which led to an increase in TEER levels compared to control cells, albeit not reaching wt-CFTR TEER levels [ 43 ]. This suggests that KLF4 is needed for epithelial integrity/polarization of normal cells expressing wt-CFTR.…”
Section: Cftr and Cell Junctionsmentioning
confidence: 99%